Electrical stimulation improved cognitive deficits associated with traumatic brain injury in rats. Issue 11 (5th October 2017) - Zheng, Zhi‐tong; Dong, Xin‐long; Li, Ya‐dan; Gao, Wei‐wei; Zhou, Yuan; Jiang, Rong‐cai; Yue, Shu‐yuan; Zhou, Zi‐wei; Zhang, Jian‐ning
Abstract: Introduction: Cognitive deficits associated with traumatic brain injury (TBI) reduce patient quality of life. However, to date, there have been no effective treatments for TBI‐associated cognitive deficits. In this study, we aimed to determine whether electrical stimulation (ES) improves cognitive deficits in TBI rats. Methods: Rats were randomly divided into three groups: the Sham control group, electrical stimulation group (ES group), and No electrical stimulation control group (N‐ES group). Following fluid percussion injury, the rats in the ES group received ES treatment for 3 weeks. Potent cognitive function‐relevant factors, including the escape latency, time percentage in the goal quadrant, and numbers of CD34 + cells, von Willebrand Factor + (vWF + ) vessels, and circulating endothelial progenitor cells (EPCs), were subsequently assessed using the Morris water maze (MWM) test, immunohistochemical staining, and flow cytometry. Results: Compared with the rats in the N‐ES group, the rats in the ES group exhibited a shorter escape latency on day 3 ( p = .025), day 4 ( p = .011), and day 5 ( p = .003), as well as a higher time percentage in the goal quadrant ( p = .025) in the MWM test. After 3 weeks of ES, there were increased numbers of CD34 + cells ( p = .008) and vWF + vessels ( p = .000) in the hippocampus of injured brain tissue in the ES group compared with those in the N‐ES group. Moreover, ES also significantly increased the number of EPCs in the peripheral blood from days 3 to 21 after TBI in the ES group ( p < .05). Conclusions: Taken together, these findings suggest that ES may improve cognitive deficits induced by TBI, and this protective effect may be a result, in part, of enhanced angiogenesis, which may be attributed to the increased mobilization of EPCs in peripheral blood. Abstract : Electrical stimulation could improve cognitive deficits induced by traumatic brain injury. This protective effect could be partially due to the enhanced angiogenesis, which may finally attribute to the increasing mobilization of the endothelial progenitor cells in peripheral blood.